Efficiency of silane gas generation in high-rate silicon etching by narrow-gap microwave hydrogen plasma. (9th December 2015) - Ohmi, Hiromasa; Funaki, Takeshi; Kakiuchi, Hiroaki; Yasutake, Kiyoshi
Abstract: The silicon (Si) etching characteristics and the related efficiency of the etched Si to generate SiH4 gas in narrow-gap high-pressure microwave H2 plasma have been investigated. It was found that cooling of the Si sample is effective to obtain a high etching rate even under high pressure conditions, and the excess temperature increase of both the gas and Si sample can be suppressed even at an input power density of more than 250 W cm −3, probably because of the narrow plasma gap. The local etching depth monotonically increased with increasing H2 pressure and input plasma power, whereas the etching weight decreased with increasing H2 pressure. By simultaneously increasing the H2 pressure and input power, a maximum Si etching rate of 38 μ m min −1 was achieved. This is considered to be related to the high H density generated in the narrow-gap microwave plasma at relatively low temperatures. The energy efficiency of Si etching and the utilization efficiency of the etched Si and H2 gas for SiH4 formation are discussed. Lower input power is favorable for high energy efficiency of Si etching. The Si utilization efficiency, which is defined as the molar ratio of generated SiH4 to etched Si, increases with decreasing average gas residence time in the plasma, whereas H2 utilization efficiency is independent of the gas residence time.